Combined magnetic and kinetic control of advanced tokamak steady state scenarios based on semi-empirical modelling. (1st May 2015) - Moreau, D.; Artaud, J.F.; Ferron, J.R.; Holcomb, C.T.; Humphreys, D.A.; Liu, F.; Luce, T.C.; Park, J.M.; Prater, R.; Turco, F.; Walker, M.L.
Abstract: This paper shows that semi-empirical data-driven models based on a two-time-scale approximation for the magnetic and kinetic control of advanced tokamak (AT) scenarios can be advantageously identified from simulated rather than real data, and used for control design. The method is applied to the combined control of the safety factor profile, q ( x ), and normalized pressure parameter, β N, using DIII-D parameters and actuators (on-axis co-current neutral beam injection (NBI) power, off-axis co-current NBI power, electron cyclotron current drive power, and ohmic coil). The approximate plasma response model was identified from simulated open-loop data obtained using a rapidly converging plasma transport code, METIS, which includes an MHD equilibrium and current diffusion solver, and combines plasma transport nonlinearity with 0D scaling laws and 1.5D ordinary differential equations. The paper discusses the results of closed-loop METIS simulations, using the near-optimal ARTAEMIS control algorithm (Moreau D et al 2013 Nucl. Fusion 53 063020 ) for steady state AT operation. With feedforward plus feedback control, the steady state target q -profile and β N are satisfactorily tracked with a time scale of about 10 s, despite large disturbances applied to the feedforward powers and plasma parameters. The robustness of the control algorithm with respect to disturbances of the H&CD actuators and of plasma parameters such as the H-factor, plasma density and effective charge, is also shown.